الإصلاح في القرآن: استكشاف المفهوم، وبناء النظرية - التيجاني عبد القادر حامد (International Institute of Islamic Thought, 2011)
لهذه الورقة هدفان: تحليل مفهوم "الإصلاح" الذي تكرر ذكره في القرآن الكريم؛ والنظر في إمكانية استخدام ذلك المفهوم، وشبكة المفاهيم المعاضدة إطاراً نظرياً و"نموذجاً تفسيرياً" لتفسير الظواهر الاجتماعية والسياسية، وتوقع مآلاتها المستقبلية. تتضمن الورقة تحليلاً متعمقاً لمفهوم "الإصلاح" ومشتقاته، والأوصاف والصور المصاحبة له، واستقصاء أبعاده الحيوية والكونية والاجتماعية. وتختتم الورقة باستظهار النموذج التفسيري، وبتوضيح نتائج العملية الإصلاحية، مع الإشارة لنوعية الدراسات التي يمكن أن تكمل موضوعها، والسياسات التي يمكن أن تبنى عليها. This paper has two goals: analyzing the concept of islah in the Qur'an, and employing it (together with the cluster of concepts associated with it) as a theoretical framework and an explanatory paradigm that may explain the sociopolitical phenomena, and predict their future implications and outcomes. After carefully examining the Qur'anic descriptive definitions where the term islah and its derivatives are used, the paper proceeds to examine the associations and images that accompany these descriptions, and to trace them to their possible bio-psychical settings, and cosmological and social dimensions. The paper then concludes with showing the possible outcomes and implications of islah.